2018
DOI: 10.1292/jvms.17-0308
|View full text |Cite
|
Sign up to set email alerts
|

Trematode infections in farm animals and their vector snails in Saint Martin’s Island, the southeastern offshore area of Bangladesh in the Bay of Bengal

Abstract: The prevalence of snail-borne trematode (SBT) infections in farm animals on the offshore Saint (St.) Martin’s Island of Bangladesh were 68.9% for cattle, 76.7% for buffaloes, 56.3% for goats, respectively. Examination of fecal samples showed that paramphistomes infection was the most common at 50.5% followed by schistosomes at 23.7% and Fasciola at 2.3%. Fasciola infection was found in cattle (1.9%) and buffaloes (16.7%) but not in goats. Schistosome infection in cattle, buffaloes and goats were 31.1, 6.7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…Our findings noted that 20% (95% CI: 15–25%) of the livestock populations are affected by Fascioliasis ( Figure 3 ), indicating a significant public health concern as an agro-based country. Recent study revealed that snail-borne trematode (SBT) infections were 76.7% for buffaloes, 68.9% for cattle, and 56.3% for goats, respectively, in farm animals on the offshore Saint Martin's Island of Bangladesh ( Yasin et al., 2018 ). Besides, several studies reported that Bangladesh is the harbor land for Fasciola spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings noted that 20% (95% CI: 15–25%) of the livestock populations are affected by Fascioliasis ( Figure 3 ), indicating a significant public health concern as an agro-based country. Recent study revealed that snail-borne trematode (SBT) infections were 76.7% for buffaloes, 68.9% for cattle, and 56.3% for goats, respectively, in farm animals on the offshore Saint Martin's Island of Bangladesh ( Yasin et al., 2018 ). Besides, several studies reported that Bangladesh is the harbor land for Fasciola spp.…”
Section: Discussionmentioning
confidence: 99%
“…Los animales menores de un año no mostraron evidencia de la infección, pero aun así no se encontró asociación estadística con respecto a la edad de los animales. La relativa mayor prevalencia de F. hepatica en animales mayores de 12 meses se puede explicar por el hecho de un mayor tiempo de exposición a la infección (Yasin et al, 2018). Por otro lado, el ciclo de vida de este parásito requiere entre 2 y 3 meses para el desarrollo de las larvas (Chaparro et al, 2016…”
Section: Resultados Y Discusiónunclassified
“…may be attributed to the grazing behaviour of animals. As small ruminants show a distinct aversion to immersion in water even avoiding walking through it, this may reduce their potential for exposure of the species (Yasin et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, due to lack of enough pasture land, animals reared by scavenging system use communal land for grazing. The snail intermediate hosts are also present at the water bodies of these locations and are likely to be contaminated with the infective stage of trematode parasites (Yasin et al., 2018). On the other hand, animals reared in semi‐intensive system are provided selective fodder, which have less chance of getting infected by the infective stage of flukes (Nzalawahe et al., 2014).…”
Section: Discussionmentioning
confidence: 99%